Peculiarities of physical fitness and body composition of students engaged and not engaged in sports - I.J. Zuoziene (Physical Education of Students, 2013)
Peculiarities of students’ physical fitness and body composition were identified through an international research project including Lithuania, Poland and Belorussia. The article deals with the data of research carried out in Lithuania. The study included 207 students (aged 19.7 ± 1.3). It was established that students engaged in sports demonstrated higher results in speed and agility tests compared to their counterparts not engaged in sports (p